Effects of purwoceng (Pimpinella alpina) root extract administered during pregnancy on offspring growth and female reproductive development in rats - Aryani Sismin Satyaningtijas; Pudji Achmadi; Damiana Rita Ekastuti; Isdoni Bustamam; Koekoeh Santoso; Hera Maheshwari; Maulana Sydik; Muh Alwi Amnur; Wahyu Sri Wulandari; Ronald Tarigan (ARSHI Veterinary Letters, 2026)
Purwoceng (Pimpinella alpina) is a medicinal plant with phytoestrogenic properties that may affect reproductive development. This study aimed to evaluate the effects of purwoceng root extract administered during pregnancy on offspring growth and sexual maturation in rats. The measured parameters were body weight gain in male and female offspring, age at vaginal opening, and estrous cycle length in female offspring. The results demonstrated that maternal administration of purwoceng extract increased body weight gain in offspring and accelerated the onset of puberty, as indicated by earlier vaginal opening, while no significant differences were observed in estrous cycle length. In conclusion, purwoceng root extract exhibits anabolic and estrogenic effects that promote growth and sexual maturation in offspring without disrupting the normal estrous cycle.